Sensitivity Training of Inclusive Campus Services for Students with Disabilities at Mercu Buana University - Harahap, Rachmita Maun (Universitas Mercu Buana, 2024)
Universitas Mercu Buana (UMB) has not declared itself an inclusive higher learning institution. However, there has been a long-standing concern for specific students with disabilities. More than 27 students with disabilities have been admitted to UMB. As the university has not provided accommodation facilities that cater to different disabilities, some students with disabilities may take 5–6 years to graduate because they are unable to actualize themselves fully. For UMB to set an example and serve as a model for inclusive campuses in Indonesia, the activity's goals are to raise awareness of the need for inclusive campuses and provide sensitivity training for the academic community regarding special services for students with disabilities. The strategies for implementing this activity include promoting the development of inclusive campus policies, holding sensitivity training for special services for students with disabilities for the UMB academic community, and assessing and evaluating the training participants. The participants have gained an understanding of the perspectives of students with disabilities and how to interact with them through simulations as a result of this exercise. Following the needs of students with various disabilities, the academic community aims to prepare the availability of reasonable accommodation facilities. The participants could absorb, process, and understand what the two presenters had to say